The Analysis of Lucy's Personality in Narnia the Lion, the Witch and the Wardrobe Film - Fatqu Rofiqoh Dewi; Sulis Nurpitasari (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
Personality is a form of behavior that is shown by a person as a form of self-introduction that is influenced by customs and culture in the environment where humans live and interact. This research was talking about what personality that Lucy has. The researcher tries to find Lucy’s Personality on Narnia the Lion the Witch and the Wardrobe film, which is including on extrovert or introvert child. The purpose of this research is to understand personality in young learners as like Lucy Pevensie. In research, researchers use qualitative research. Qualitative research is research that does not intersect with numbers (count) but rather observes the object under study and then provides a description of the object under study. Researchers use descriptive analysis method, which is to describe phenomena that occur naturally or man-made which focus more on character and quality. The data source that the researcher uses in this thesis is Narnia the Lion the Witch and The Wardrobe film. The researcher used data collection techniques by watching Narnia the Lion the Witch and The Wardrobe film, identifying all the scenes played by Lucy Pevensie and the dialogue in the film to get the data, grouping the data that addresses the problem to be studied, analyzing the data that has been collected and make conclusions due to research. After the data has been collected, the researcher analyzed the data by watching the scene played by Lucy Pevensie and paying attention to the dialogue from the film